2004
DOI: 10.1182/blood-2004-03-1067
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 responsiveness defines a subset of CD8 T cells poised to kill

Abstract: CD8 T cells play a key role in host defense against intracellular pathogens. Efficient migration of these cells into sites of infection is therefore intimately linked to their effector function. The molecular mechanisms that control CD8 T-cell trafficking into sites of infection and inflammation are not well understood, but the chemokine/chemokine receptor system is thought to orchestrate this process. Here we systematically examined the chemokine receptor profile expressed on human CD8 T cells. Surprisingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 41 publications
4
84
0
Order By: Relevance
“…Indeed, recent studies have identified a subset of human CD8 + T cells that express CXCR1, respond to IL-8 and have cytotoxic function [22,23]. Memory CD8 + T cells do not express this receptor [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have identified a subset of human CD8 + T cells that express CXCR1, respond to IL-8 and have cytotoxic function [22,23]. Memory CD8 + T cells do not express this receptor [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In uninfected mice the mean percentage of CD27 -cells within the lung CD8 + T-cell population was 11% and upon influenza infection this increased to 20% at day 9 and 29% at day 20 after infection ( Table 1). The increase in the lung at day 9 was possibly due to nonspecific migration of CD8 + CD27 -memory T cells in response to inflammatory mediators produced in inflamed lung [38][39][40] because at this time point nearly Liver 208 Table 2. In a CD27 x CD62L dot plot three subpopulations were identified: R1, CD62L + CD27 + ; R2, CD62L -CD27 + ; R3, CD62L -CD27 -.…”
Section: Cd27 Expression Is Lost After Repetitive Stimulation In Vivomentioning
confidence: 98%
“…IL-8 has been shown to recruit and activate neutrophil granulocytes [24], and stimulate IL-2-activated natural killer cells [25] and lymphokine-activated killer cells [26]. Recently, a subset of CD8 + T lymphocytes has been described, which is poised for immediate cytotoxicity and early recruitment by IL-8 into sites of innate immune activation [27,28]. Induction of IL-8 by muropeptides, therefore, may define a bacterial-specific response to enhance clearance from the infected host.…”
Section: Discussionmentioning
confidence: 99%